(untitled) (Journal of NELTA, 2021)
Despite a growing body of research on language test impact, little is known about the impacts of a high-stakes test on students in the Nepalese context. This paper reports on a study that explored the impact of an English as a foreign language (EFL) test on students in Nepal. The data generated through a student survey (n=247), oral diaries (n=72) and semi-structured interviews (n=24) with students and parents indicate severe impact of the English test on students. The majority of students reported that they were under tremendous pressure to perform well on the test and they had a high level of anxiety associated with the test. There were several indications that students had test related anxiety mainly because of their perception that poor performance on the test has negative eﬀects on their social prestige and on career prospects. Additional reasons of their anxiety included high expectations from their parents and teachers. Finally, some of the pressing policy, pedagogical and research implications of the findings are discussed.